APPLICATION OF GIS TECHNOLOGIES IN HISTORICAL ANALYSIS OF RIVER SYSTEMS ON AN EXAMPLE BELGOROD REGION - A. N. Petin; M. A. Petina; M. G. Lebedeva; V. G. Belevantsev (InterCarto. InterGIS, 2015)
Historical and cartographic analysis with the use of GIS technologies showed that in the basin of Pena river (the basin of Dnepr) in the late nineteenth century the decline of the river network was 27%, and by the end of the XX century – 29% in comparison with the end of the XVIII century In the basin of the Black Kalitva (Don river basin), these values amounted to 67% and 75% respectively. The maximum degradation marks of the river network in the basin of the Black Kalitva were traced for the period from the 1 780s through the 1880s. In both observed basins the rivers of 3– 5 orders were exposed by the maximal degradation as a result of destroying from the mid-nineteenth century a considerable part of the ravine forests in their source areas (west of the region) and practically complete agricultural development of natural steppes in the east of the territory.